Passing and tackling qualities discriminate developmental level in a rugby league talent pathway - Pearce, L. A.; Sinclair, W. H.; Leicht, A. S.; Woods, C. T. (International Journal of Performance Analysis in Sport, 2019)
This study compared the passing and tackling qualities of talent identified rugby league (RL) players within a developmental pathway. From a total of 88 players, three developmental levels were defined: under 18 years (U18; n = 27), under 20 years (U20; n = 29), and state league (SL; n = 32). All participants performed skills tests that measured passing and tackling qualities. A MANOVA modelled the main effect of developmental level (three levels: U18, U20 and SL) with receiver operating characteristic (ROC) curves then built for variables that showed a significant effect. A significant effect was noted for passing over four to 12 m (V= 0.303, F = 2.406, P< 0.05), with the SL players outperforming their U18 and U20 counterparts. The ROC curves generated an area under the curve of greater than 63% for each passing test criterion, indicating greater than chance discrimination. The choice of tackle and technical execution of tackle discriminated the SL players from the U18 and U20 groups. Utilising the criteria for objective measures for fundamental skill assessment throughout RL development is likely to assist with the junior-to-senior transition of talented RL players.